Hodgkin Lymphoma in Children and Adolescents: Advances in Pathology, Diagnosis, and Treatment Strategies (Indian Journal of Medical and Paediatric Oncology, 2020)
Strategies used for the treatment of children with Hodgkin lymphoma (HL) over the last four decades have resulted in excellent long-term survivals. However, the short- and long-term treatment-associated morbidities were high. In an attempt to reduce complications, the current treatment strategies apply initial risk stratification principles based on certain host and tumor risk factors to help assign patients to the appropriate risk group and tailor therapy based on response to chemotherapy (CTR). Radiotherapy (RT) was only given to certain groups of patients who show suboptimal response to CTR. Enrollment of patients in clinical trials allowed testing newer treatment strategies, which has improved the outcome significantly. High-dose CTR with stem cell support remains the mainstay of treatment for relapsed and refractory HL. Newer targeted medications are being increasingly used for the treatment of patients with relapsed and refractory HL, but results are variable. In this review report, we give extensive account about the pathophysiology, clinical presentation, histopathological diagnosis, modern investigation techniques, the most recent risk adapted treatment strategies, and the use and effect of novel medications. In addition, we discuss in details the short- and long-term therapy-related complications and future prospects in the management of HL.
Keywords: 18Fluorodeoxyglucose–positron emission tomography scan; chemotherapy; Hodgkin lymphoma; pathological classification; radiotherapy; staging system